P626 Development of a model of 3D imaging for the pre-operative planning of TaTME. (16th January 2018) - Sahnan, K; Pellino, G; Adegbola, S O; Tozer, P J; Chandrasinghe, P; Misovikc, D; Hompes, R; Hart, A L; Warusavitarne, J; Lung, P F
Abstract: Background: Transanal TME (TaTME) is a new addition to the approaches in rectal surgery. TaTME requires advanced technical skills and, more importantly, knowledge of the pelvic structures, planes, and spaces as they are encountered moving cephalad from the perineum. We have developed a technique for producing 3D reconstructions of the anorectum and associated anatomy, to aid peri-operative planning and understanding of the anatomy crucial to TaTME surgery. Methods: A patient was scheduled for single incision laparoscopy surgery (SILS) TaTME completion proctectomy and ileoanal pouch formation for ulcerative colitis. Standard axial T2-weighted Spectral Attenuated Inversion Recovery (SPAIR) and sagittal T2-weighted MRI sequences were obtained and digital imaging and communications in medicine (DICOM) images were imported into a validated open-source segmentation software. 1 A specialist consultant gastrointestinal radiologist manually segmented the following structures: sphincter complex; rectosigmoid colon; levator plate, bladder, ureters, urethra and prostate. Each mesh was imported into another open-source system, MeshLab V1.3.3.1 as Stereolithography (STL) files for mesh smoothing to be applied. Individual labels were applied to each anatomical structure. Results: Segmentation took approximately 15 min and an additional 10 min was required for smoothing and applying colour and transparency of the anatomical structures to emphasise surgically relevant anatomy. In Figure (A) provides an overview of the anatomy showing a relatively straight and posterior direction of the rectum as it descends into the pelvis; (B) provides insight into the relation between internal sphincter/rectum and the prostate/urethra. Distance between structures and relative proximity can be easily understood. Figure (C) shows the clearance between low rectum and both ureters, whilst (D) shows an anterior oblique view of the sphincter complex and the urethra. Conclusions: Surgeons currently use a combination of MRI scans, reports and discussion with radiologists to better understand anatomy. The use of these reconstructions in the MDT, in clinic and in the operating theatre could be useful to better communicate complex rectal anatomy, identify areas of difficulty and aid surgical planning. Our reconstructions present a present a cost-neutral solution to better visualise the anatomy they represent the first step towards innovation in TaTME surgery.